Research approaches in master-based teacher education preparing student teachers for professional work - Antonsen, Yngve; Toom, Auli; Ulvik, Marit; Drageset, Ove Gunnar; Olsen, Knut Rune; Hjardemaal, Finn Rudolf; Sæther, Kari-Anne (Frontiers in Education, 2024)
Student teachers have been found to be critical towards the research approaches they learned from their master's-based teacher education programmes. Our aim is to discuss how certain research approaches learnt during a five-year academic master's level teacher education, may bring student teachers close to practice and provide them with conceptual and practical tools for a thorough understanding of the practice of teaching. The argumentation is based on an elaboration of master's-based teacher education programs in Finland and Norway and the essential characteristics of teachers' work. We elaborate on student teachers' need to understand constative, critical and constructive research approaches. This includes critical approaches such as observations and interviews for understanding and interpretation, and constructive approaches such as action research and lesson studies. Finally, we argue that, through these approaches, student teachers make use of research knowledge in teachers' work with an inquiring orientation as well as develop and change their practice.